Characterizing burnout among healthcare epidemiologists in the early phases of the COVID-19 pandemic: A study of the SHEA Research Network. Issue 1 (17th March 2023) - Smith, Tucker John Guy; Pryor, Rachel; Hota, Susy S.; Haessler, Sarah D.; Deloney, Valerie M.; Bearman, Gonzalo
Abstract: A multisite research team proposed a survey to assess burnout among healthcare epidemiologists. Anonymous surveys were disseminated to eligible staff at SRN facilities. Half of the respondents were experiencing burnout. Staffing shortages were a key stressor. Allowing healthcare epidemiologists to provide guidance without directly enforcing policies may improve burnout.